Massline Visualization of Double-Diffusive Natural Convection inside a Cavity Filled with Nanofluid Subjected to Heat Flux and Transverse Magnetic Field - O. Ghaffarpasand (Journal of Applied Fluid Mechanics, 2017)
In the present work, massline visualization technique as an innovative method is utilized to deepen our insights into the problem of double-diffusive natural convection of nanofluids. The effects of inclination angle and strength of the external magnetic field on one side and heat flux coefficient on the other side on the masslines, isoconcentrations, isotherms, heat and mass transfer are fairly studied and discussed. The governing equations together with appropriate boundary conditions are solved numerically using a finite difference method in a square lid-drive cavity filled with Cu-water nanofluid. Four pertinent parameters are studied these; the orientation angle of the magnetic field (λ = 0◦ − 270◦), Hartman number (Ha = 0 − 100), heat flux coefficient (ε= 1 − 200), and nanoparticle volume fraction (ϕ = 0 − 10%). Results indicate that the orientation and strength of applied magnetic field can be considered as the key parameters in controlling double-diffusive natural convection. It is also found that the existence of metallic nanoparticles in the presence of magnetic field can play different roles in the heat and mass transfer variations. Meanwhile, high amount of heat flux injected through the cavity has an aiding effect on the convective current of mass within the cavity. Results also indicate that nanofluid has relatively smaller massline circulation loops than pure fluid.